Patient Characteristics and Participation in a Genetic Study: A Type 2 Diabetes Cohort. (January 2014) - Amiri, Loabat; Cassidy-Bushrow, Andrea E.; Dakki, Heather; Li, Jia; Wells, Karen; Oliveria, Susan A.; Yood, Marianne Ulcickas; Thomas, Abraham; Lanfear, David E.
Background: Recruitment of large, diverse populations into genetic studies remains challenging. Potential strategies to overcome limitations include leveraging electronic health data and minimizing patient burden. We sought to describe the overall participation rate and identify characteristics associated with participation in a genetic substudy of patients with type 2 diabetes mellitus, in which patients were identified via electronic hospital data and asked to participate by providing DNA samples by mail. Methods: During a phone interview, participants (n = 455) were asked to take part in a genetic substudy. Subjects verbally consenting were mailed saliva collection kits and written consent forms. We examined demographic and clinical variables associated with verbal consent and DNA kit return using logistic regression. Results: Overall, 90% (n = 410) verbally consented to the genetic substudy during interviews. However, of those consenting, only 70% returned the DNA kit (n = 287). Among those consenting, after covariate adjustment, male sex (odds ratio [OR], 1.70; 95% confidence interval [CI], 1.09–2.65), African American race (OR, 0.61; 95% CI, 0.39–0.95), hemoglobin A1c (HbA1c ) (OR, 0.87; 95% CI, 0.75–1.00), and physical activity (OR, 0.58; 95% CI, 0.37–0.91) were significantly associated with DNA kit return. Conclusions: To our knowledge, we are the first to demonstrate an inverse association between HbA1c and participation in genetic research, potentially indicating a compliance-related trait needing further exploration. The DNA kit return rate being notably lower than the verbal consent rate suggests that the greater convenience of a telephone/mail-in process did not drastically enhance full participation. Direct comparison to in-person donation may be warranted.